2007 46th IEEE Conference on Decision and Control 2007
DOI: 10.1109/cdc.2007.4434780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of methods for multivariable frequency response function estimation in closed loop

Abstract: Estimation methods for the multivariable frequency response function are analyzed, both in open and closed loop. Approximate bias and covariance expressions are derived for the closed loop case. The usefulness of these expressions is illustrated in simulations of an industrial robot where three dierent estimators are compared. The choice of estimator depends on the signal-to-noise ratio as well as the measurement setup and a bias-variance trade-o.Keywords: Nonparametric identication, Multivariable systems, Clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Various aspects of the procedure are also treated in Wernholt and Gunnarsson (2006b), Wernholt and Löfberg (2007), Wernholt and Gunnarsson (2007) and Wernholt and Moberg (2007). Using an FRF-based procedure allows for data compression, unstable systems are handled without problems, it is easy to validate the model such that all important resonances are captured, and model requirements in the frequency domain are also easily handled.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various aspects of the procedure are also treated in Wernholt and Gunnarsson (2006b), Wernholt and Löfberg (2007), Wernholt and Gunnarsson (2007) and Wernholt and Moberg (2007). Using an FRF-based procedure allows for data compression, unstable systems are handled without problems, it is easy to validate the model such that all important resonances are captured, and model requirements in the frequency domain are also easily handled.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…See also, e.g., Wernholt and Gunnarsson (2007) and Wernholt and Moberg (2007) for other FRF estimators for multivariable systems.…”
Section: Frf Estimationmentioning
confidence: 99%
“…The JIO estimator is asymptotically unbiased, and the bias of the other estimators varies depending on the SNR. A recent study on the rst three estimators can be found in Wernholt and Gunnarsson (2007). See also , Guillaume (1998), andVerboven (2002).…”
Section: Introductionmentioning
confidence: 99%
“…The H 1 -estimator is the best estimator if the output noise is much larger compared to the input noise (which is assumed zero in this chapter) [43]. If the system is excited using an orthogonal random phase multisine signal, the variance of the FRF estimates is minimized [65]. A scalar random phase multisine signal x(t) can be written as …”
Section: The Estimation Methodsmentioning
confidence: 99%
“…The method is adopted from [65] and is summarized in subsection 6.3.1. The use of this method results in avoiding leakage effects and minimizing the variance of the FRF estimates.…”
Section: Frequency Response Function Estimatesmentioning
confidence: 99%